Evaluation of Antilipolytic, Antioxidant and Antibacterial Activities of Selected Ferns - Jarial, Rini; Singh, Lakhveer; Thakur, Sveta; Zularisam, A. W.; Mimi Sakinah, A. M.; S. S., Kanwar (Open Science Publishers LLP Inc., 2017)
In the present study, three ferns were used (Adiantum capillus-veneris Cheilanthes albomarginata and Asplenium pumilum,) to identify their functional compounds to reduce obesity. The methanolic fern-extract (MFE) of these ferns was assessed for anti-bacterial activity by measuring inhibition zones against a panel of pathogenic bacterial strains using the agar diffusion method. MFE at a concentration of 25 μg /ml showed marked anti-bacterial activity against all bacterial strains (6mm to 23mm) zone of inhibition and was greatest against Enterobacter sp (23 mm). Out of these, the MFE of the A. veneris fern extract had the best MIC values of 2.25 μg /ml against S. aureus and Enterobacter sp. respectively. It had an inhibitory concentration (69.9 %) for 2, 2-diphenylpicryl-1-picryl-hydrazyl (DPPH) scavenging activity. The MFE of the A. veriens also possessed good anti-lipolytic activity (76.5%) against a porcine pancreatic lipase (PPL) and cholesterol oxidase inhibition (89%). The hemolytic activity of A. veneris was found to be 27.6% at 6.25 µg/mL of MFE. This result showed that the MFE of A. veriens is not only a potent source of natural anti-oxidants and anti-bacterial activities but also possesses efficient cholesterol degradation and anti-lipolytic activities, which would be beneficial in body weight management.